2015
DOI: 10.1074/jbc.m114.634063
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Parkin, PINK1, and α-Synuclein on Stress-induced Mitochondrial Morphological Remodeling

Abstract: Background: Parkin is proposed to maintain mitochondrial QC through promoting mitophagy. Results: Under moderate mitochondrial stress conditions, parkin stimulates mitochondrial fusion instead of mitophagy by catalyzing K63-linked ubiquitination and inactivating ␣-synuclein. Conclusion: Parkin, PINK1, and ␣-synuclein form a regulatory circuit to regulate mitochondrial stress response. Significance: This study provides a physiological context to functionally connect key PARK genes in the pathogenesis of Parkins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 46 publications
(43 reference statements)
4
69
0
2
Order By: Relevance
“…Some recent studies have indicated that PINK1 accumulation, along with Parkin recruitment on damaged mitochondria, depends on the bioenergetic state of the cell, and ATP may have a key involvement in this process 132,133. Furthermore, other studies have indicated complex interactions of Parkin, PINK1 and α-synuclein in regulating mitochondrial dynamics and mitophagy 134,135. Overall, it appears that altered mitophagy and mitochondrial dynamics play a key role in PD pathogenesis, with the involvement of Parkin, PINK1 and α-synuclein, but the molecular scenario is far from clear as of now.…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…Some recent studies have indicated that PINK1 accumulation, along with Parkin recruitment on damaged mitochondria, depends on the bioenergetic state of the cell, and ATP may have a key involvement in this process 132,133. Furthermore, other studies have indicated complex interactions of Parkin, PINK1 and α-synuclein in regulating mitochondrial dynamics and mitophagy 134,135. Overall, it appears that altered mitophagy and mitochondrial dynamics play a key role in PD pathogenesis, with the involvement of Parkin, PINK1 and α-synuclein, but the molecular scenario is far from clear as of now.…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…Under moderate stress conditions PINK1 and Parkin reportedly regulate generation of mitochondria-derived vesicles to degrade oxidized mitochondrial components [20]. Similarly, low dose treatment with the mitochondrial uncoupler CCCP results in Parkin-mediated fusion, which limits mitochondrial damage and thus mitophagy in neurons [21] (see next paragraph). Higher doses of CCCP reportedly promote Parkin recruitment and mitophagy, which is antagonized by Parkin interaction with antiapoptotic Bcl-2 proteins (Bcl-xL, Mcl-1, Bcl-w) [22**].…”
Section: Mitochondrial Dynamics Mitochondrial Quality Control and Cementioning
confidence: 99%
“…PARK2 controls the cell cycle by acting as a master regulator of multiple G1/S cyclins. Using systems mainly geared towards examining neural biology, several studies have shown that PARK2 plays a role in mitochondrial maintenance and turnover [12], [13], [14]. However, the full extent of PARK2’s functions and how inactivation of PARK2 promotes tumor growth is unknown.…”
Section: Introductionmentioning
confidence: 99%